Equilibrium strategies of channel structure and RFID technology deployment in a supply chain with manufacturer encroachment. Issue 6 (19th March 2022) - Zhang, Li-Hao; Tian, Lin; Chang, Lu-Yu
Abstract : The rapid growth of online marketplaces and the advance of Internet technology have enabled manufacturers to more easily engage in direct selling through their own online stores. However, as any retail channel suffers misplacements, the manufacturer's direct sales channel will also face a critical inventory misplacement problem if it chooses encroachment. Radio-frequency identification (RFID) proven to be the most effective technology to eliminate the inventory misplacement problem. This paper investigates the strategic interaction between manufacturer encroachment and RFID deployment decisions in a supply chain consisting of a manufacturer and a reseller. We find that the manufacturers' encroachment strategies are determined by channels' misplacement rates, RFID deployment decisions and channel competition intensity. Specifically, the retail (direct) channel's misplacement problem encourages (discourages) the manufacturer to encroach; in addition, if only the retail (if it is direct) channel employs RFID, the encroachment cost threshold increases (decreases) with the RFID tag price; moreover, the more intense the channel competition is, the less likely the manufacturer will be to encroach. Further, when encroachment has occurred, channel competition will be a crucial factor in the direct channel's RFID deployment decision, but it will not affect the deployment of RFID in the retail channel.